2016
DOI: 10.1007/s10120-016-0653-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features of Siewert type II adenocarcinoma: comparison of gastric cardia adenocarcinoma and Barrett’s esophageal adenocarcinoma following endoscopic submucosal dissection

Abstract: Siewert type II adenocarcinoma encompasses two types of cancers with different etiologies: GCA and BEA. Although there are no significant differences in lifestyle-related background factors between GCA and BEA, BEA is a risk factor for noncurative resection via ESD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 39 publications
(37 reference statements)
2
31
0
Order By: Relevance
“…It is well known that differentiated mucosal cancer in early gastric cancer without lymphovascular involvement and ulceration exhibits almost no metastasis [12, 22]. Osumi et al [9] suggested that Barrett’s adenocarcinoma has a higher malignant potential but exhibits similar outcomes to gastric cardiac cancer. In addition, an improved 5-year survival rate was observed in ESD for Barrett’s adenocarcinoma than in ESD for squamous cell carcinoma (88.9 vs. 75.9%), though a statistical difference was not reported [23].…”
Section: Indication Of Esdmentioning
confidence: 99%
See 4 more Smart Citations
“…It is well known that differentiated mucosal cancer in early gastric cancer without lymphovascular involvement and ulceration exhibits almost no metastasis [12, 22]. Osumi et al [9] suggested that Barrett’s adenocarcinoma has a higher malignant potential but exhibits similar outcomes to gastric cardiac cancer. In addition, an improved 5-year survival rate was observed in ESD for Barrett’s adenocarcinoma than in ESD for squamous cell carcinoma (88.9 vs. 75.9%), though a statistical difference was not reported [23].…”
Section: Indication Of Esdmentioning
confidence: 99%
“…This classification includes not only adenocarcinoma but also squamous cell carcinoma [9, 13]. On the other hand, Siewert type II tumors, located 1 cm above and 2 cm below the EGJ, are considered true cardiac adenocarcinomas arising from the EGJ epithelium [2, 9, 11, 13].…”
Section: Definition Of Egj Adenocarcinoma and Barrett’s Adenocarcinomamentioning
confidence: 99%
See 3 more Smart Citations